Effects of Sunitinib and Other Kinase Inhibitors on Cells Harboring a PDGFRB Mutation Associated with Infantile Myofibromatosis - Sramek, Martin; Neradil, Jakub; Macigova, Petra; Mudry, Peter; Polaskova, Kristyna; Slaby, Ondrej; Noskova, Hana; Sterba, Jaroslav; Veselska, Renata (International journal of molecular sciences, 2018)
Infantile myofibromatosis represents one of the most common proliferative fibrous tumors of infancy and childhood. More effective treatment is needed for drug-resistant patients, and targeted therapy using specific protein kinase inhibitors could be a promising strategy. To date, several studies have confirmed a connection between the p.R561C mutation in gene encoding platelet-derived growth factor receptor beta (PDGFR-beta) and the development of infantile myofibromatosis. This study aimed to analyze the phosphorylation of important kinases in the NSTS-47 cell line derived from a tumor of a boy with infantile myofibromatosis who harbored the p.R561C mutation in PDGFR-beta. The second aim of this study was to investigate the effects of selected protein kinase inhibitors on cell signaling and the proliferative activity of NSTS-47 cells. We confirmed that this tumor cell line showed very high phosphorylation levels of PDGFR-beta, extracellular signal-regulated kinases (ERK) 1/2 and several other protein kinases. We also observed that PDGFR-beta phosphorylation in tumor cells is reduced by the receptor tyrosine kinase inhibitor sunitinib. In contrast, MAPK/ERK kinases (MEK) 1/2 and ERK1/2 kinases remained constitutively phosphorylated after treatment with sunitinib and other relevant protein kinase inhibitors. Our study showed that sunitinib is a very promising agent that affects the proliferation of tumor cells with a p.R561C mutation in PDGFR-beta.
Keywords: U0126; protein kinase inhibitors; myofibromatóza; nádorové buněčné linie; Sunitinib; platelet-derived growth factor receptor; Protein Kinase Inhibitors; FR180204; targeted therapy; Phosphorylation; kojenec; Receptor, Platelet-Derived Growth Factor beta; infantile myofibromatosis; růstový faktor odvozený z trombocytů - receptor beta; mužské pohlaví; butadieny; mutace; Infant; Cell Proliferation; Cell Line, Tumor; sunitinib; dítě; Child; Pyrazoles; ženské pohlaví; pyridaziny; Mutation; Humans; erlotinib; Butadienes; Erlotinib Hydrochloride; proliferace buněk; Pyridazines; inhibitory proteinkinas; fosforylace; pyrazoly; Female; Myofibromatosis; nitrily; receptor tyrosine kinases; lidé; Male; Nitriles